EFFECT OF THE CHALLENGES FACING USE OF INFORMATION AND COMMUNICATIONS TECHNOLOGY IN INVENTORY MANAGEMENT AMONGST BREWERIES IN NIGERIA - Odesola, Olusegun Timothy; Akinola, Grace (Universitas Pendidikan Indonesia, 2018)
Information and communications technology (ICT) in recent times has become a viable strategic policy option adopted by many businesses in order to compete favourably in a competitive and dynamic ICT driven market. This strategic move by business organizations is being hindered by some challenges which has invariably reduced the benefits accruable from ICT deployment for business operations especially in the inventory management. Primary data formed the methodology of the study. Descriptive and inferential statistics were used to analyze data obtained through the administration of structured questionnaire. It was established during the field survey that challenges facing the use of ICT had impacted negatively on the performance of inventory management in the Nigerian brewery industry during the period under study. It was also revealed that the cost of software was a major challenge in the industry and conclude that the identified challenges had significant effect on customers satisfaction of the firms in the Nigerian brewery industry. It is recommended that management of firms in the Nigerian brewery industry should collaborate with software developers in Nigerian to develop a software that will be a replica of ERP but should be efficient, effective and affordable for inventory management and other operations in the industry.